2021
DOI: 10.3390/pharmaceutics13091514
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Drugs and Vaccines Associated with Altered Risks and Severity of COVID-19: A UK Biobank Cohort Study of All ATC Level-4 Drug Categories Reveals Repositioning Opportunities

Abstract: Effective therapies for COVID-19 are still lacking, and drug repositioning is a promising approach to address this problem. Here, we adopted a medical informatics approach to repositioning. We leveraged a large prospective cohort, the UK-Biobank (UKBB, N ~ 397,000), and studied associations of prior use of all level-4 ATC drug categories (N = 819, including vaccines) with COVID-19 diagnosis and severity. Effects of drugs on the risk of infection, disease severity, and mortality were investigated separately. Lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 101 publications
0
11
0
1
Order By: Relevance
“…Of the 92 full-text articles identified, 58 were excluded because they did not meet the inclusion criteria, and two others were obtained from the references. The remaining 36 articles reported on 55,996,841 subjects outcomes were included in this analysis [21–56] . None of the participants had received COVID-19 vaccination during the study period.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 92 full-text articles identified, 58 were excluded because they did not meet the inclusion criteria, and two others were obtained from the references. The remaining 36 articles reported on 55,996,841 subjects outcomes were included in this analysis [21–56] . None of the participants had received COVID-19 vaccination during the study period.…”
Section: Resultsmentioning
confidence: 99%
“…Data were abstracted by four authors (WS, HM, ZG, and QC) from 34 studies, ( Abu-Jamous et al, 2020 ; Alamdari et al, 2020 ; Giacomelli et al, 2020 ; Lodigiani et al, 2020 ; Russo et al, 2020 ; Sahai et al, 2020 ; Tremblay et al, 2020 ; Chow et al, 2021a ; Chow et al, 2021b ; Connors et al, 2021 ; Fröhlich et al, 2021 ; Haji Aghajani et al, 2021 ; Ho et al, 2021 ; Kim et al, 2021 ; Liu et al, 2021 ; Meizlish et al, 2021 ; Merzon et al, 2021 ; Mura et al, 2021 ; Osborne et al, 2021 ; Pan et al, 2021 ; Sisinni et al, 2021 ; Son et al, 2021 ; Xiang et al, 2021 ; Yuan et al, 2021 ; Zhao et al, 2021 ; Zhou et al, 2021 ; Al Harthi et al, 2022 ; Santoro et al, 2022a ; Chow et al, 2022 ; Formiga et al, 2022 ; Gogtay et al, 2022 ; RECOVERY Collaborative GroupAbbas et al, 2022 ; REMAP-CAP Writing Committee for the REMAP-CAP InvestigatorsBradbury et al, 2022 ; Sullerot et al, 2022 ), including three randomized controlled trials, ( Connors et al, 2021 ; RECOVERY Collaborative GroupAbbas et al, 2022 ; REMAP-CAP Writing Committee for the REMAP-CAP InvestigatorsBradbury et al, 2022 ), 27 retrospective studies, ( Abu-Jamous et al, 2020 ; Alamdari et al, 2020 ; Lodigiani et al, 2020 ; Russo et al, 2020 ; Sahai et al, 2020 ; Tremblay et al, 2020 ; Chow et al, 2021a ; Chow et al, 2021b ; Fröhlich et al, 2021 ; Haji Aghajani et al, 2021 ; Ho et al, 2021 ; Kim et al, 2021 ; Liu et al, 2021 ; Meizlish et al, 2021 ; Merzon et al, 2021 ; ...…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Almario et al [ 16 ] reported an increase in the likelihood of developing COVID-19 infection after PPI administration. In contrast, Xiang Y et al [ 17 ] concluded that PPI decrease the susceptibility to COVID-19. Furthermore, Ramchandran et al [ 18 ] observed increased mortality with PPI usage whereas Fan X [ 19 ] did not find an association between PPI and mortality due to COVID-19 infection.…”
Section: Introductionmentioning
confidence: 98%